Sistem Penggajian pada Sektor Publik (Studi Kasus pada Dinas Pendidikan Kota Malang) - Aresty Caesar Delanty SAR; Ari Kamayanti (Jurnal Ilmiah Mahasiswa FEB, 2013)
Economic sector in Indonesia increasingly shows development and progress particularly on the management and supervision occurred in economic activities. This development results in the advancement of the management and quality of accounting information system. Accounting information system is essential not only for the private sector, but also the public sector in to transform economic data into the accounting information which supports the implementation of the payroll system. The system is designed to handle payroll calculation and payment of salaries to civil servants, particularly in the education department. Department of Education is an organization which plays a role in dedicating their services particularly in the field of education toward the community, thus the education department requires information system for performing their activities effectively and efficiently. This study was conducted at the Department of Education of Malang City which has the purpose to understand the payroll system were implemented, the Department of Education of Malang City. Case study approach used in this study through interview, direct observation, documentation, and related literature on payroll system. The results of this study indicate that the payroll system is applied to the Department of Education Malang is good enough and are in compliance with applicable regulations, but there are still some drawbacks, namely, the lack of standard operating procedure (SOP) and there is still some work that is done manually. Therefore, researchers are trying to provide suggestions that may be useful in improving the payroll system at the Department of Education of Malang City.   Keywords: Information System, Accounting, Payroll System